Does the operating performance of the acquirer firms improve with mergers and acquisitions? an Asia-Pacific empirical study. - Goh, Kwee Shan. (2008)
The objective of this study is to assess the post-acquisition performance of acquirer firms in the Asia-Pacific region using accounting studies. Five accrual and two cash flow ratios are employed in this study; and the post-acquisition performance of acquirer firms are benchmark against firms matched on industry and size.